Residual electron spin resonance signals of quartz from the 2018 Baige dammed lake in Tibet: Implications for the identification of sediment layers caused by megafloods - Wei, Chuanyi; Yin, Gongming; Du, Jinhua; Liu, Chunru; Cheng, Li; Ji, Hao; Wang, Libin (Frontiers in Earth Science, 2023)
Residual doses may cause overestimation of electron spin resonance (ESR) ages for fluvial sediments. However, ESR residual doses in outburst megaflood sediments have rarely been evaluated. The Jinsha River, situated in the southeastern Tibetan Plateau, is characterized by active faults, narrowed canyons, and dammed lakes. Consequently, the river is a rare opportunity for a reconstruction study of outburst flood events from a paleo-dammed lake. After the destruction of the Baige dammed lake in the upper Jinsha River in 2018, outburst megafloods formed a thick diluvium that was deposited in broad valley land along the lower Jinsha River. Based on detailed field investigation and laboratory studies, preliminary hydraulics estimates and residual quartz ESR signals indicate the following. 1) Among the multiple quartz ESR centers, the Al, E1ʹ, Ti-H, and Ti-Li centers could be measured. The Ti-H center had the lowest residual dose and would provide relatively accurate ages for outburst megaflood sediment. 2) The Ti-Li and Al centers commonly used for ESR dating provide overestimates of 283 ± 42 ka ∼ 462 ± 63 ka and 1,010 ± 88 ka ∼ 1,400 ± 219 ka, respectively, for present outburst megaflood sediment. 3) The diverse ages given by the same ESR signal may be caused by various precursors of megaflood sediments, which are mainly sourced from landslide dams and from various terraces and slope sediments along the river. Results demonstrated that the apparent ESR ages observed for the outburst megaflood sediment in the southeastern Tibetan Plateau may be counterfeit, providing an age much older than its real age. This could be interpreted to mean that the narrowed lower channel makes the upper reaches of the broad valley appear lake-like, with diluvium deposits having large non-negligible residual ESR signals without enough exposure to adequate sunlight, despite having good stratification and sorting characteristics similar to those of fluvio-lacustrine sediments. Thus, abrupt reversal in quartz ESR ages in multiple centers observed in the geochronological framework of the fluvial sedimentary profile may indicate a diluvial or flood layer in the absence of other inducements.